Spot-beam effect in grazing atom-surface collisions: From quantum to classical - Frisco, Leandro (2018)
Grazing incidence fast atom diffraction (GIFAD) is a sensitive tool for surface analysis, which strongly relies on the quantum coherence of the incident beam. In this article we study the spot-beam effect, due to contributions coming from different positions of the focus point of the incident particles, which affects the coherence of GIFAD spectra. We show that the influence of the spot-beam effect on GIFAD patterns depends on the width of the surface area that is coherently lighted by the atomic beam. While for extended illuminations the spot-beam contribution plays a minor role, when a narrow surface area is coherently lighted, the spot-beam effect allows projectiles to explore different zones of a single crystallographic channel, bringing to light intra-channel interference structures. In this last case the spot-beam effect gives also rise to a non-coherent background, which deteriorates the visibility of the interference structures. We found that by varying the impact energy, while keeping the same collimating setup, it is possible to switch gradually from quantum to classical projectile distributions. Present results are compared with available experimental data, making evident that the inclusion of focusing effects is necessary for the proper theoretical description of the experimental spectra.